PERAN KODE ETIK DALAM MEMBANGUN PROFESI YANG BERMARTABAT - Witarti Rabawti, Dwityas; M. J. Ndolu, Chinta; A. G. Bhebhe, Theresia; S. Ngatu, Marselino; Snak, Stefanus; M. Enique, Yendra (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study examines the role of the code of ethics in building a reputable profession and enhancing public trust. Through literature review, field observation, and interviews with experts and practitioners, it was found that the code of ethics is an important moral foundation in maintaining the integrity and professionalism of professional members. Strict enforcement of the code of ethics helps increase public trust and preserve professional dignity. This study also identifies challenges in the implementation of the code of ethics, such as low ethical awareness and weak ethical enforcement. Recommendations include increased socialization, development of an adaptive code of ethics, and strict enforcement of ethics.